SOCIAL WORK SERVICES TO INTERNALLY DISPLACED PERSONS: INSIGHTS FROM A QUALITATIVE STUDY IN NIGERIA - Amadasun, Solomon (Social work and education, 2020)
One unique feature of the social work profession is the centrality of the person-in-environment perspective, which dictates that social work services be holistic. The purpose of this study is to examine the nature of social work services to internally displaced persons (IDPs). This research is a qualitative study, conducted with 15 social workers in Nigeria. Data were collected through a semi-structured interview with the participants in Abuja. Results show that social work services are largely inadequate to address the broad range of needs, issues, and concerns of displaced persons. Feasible suggestions that considers the intersectionality between people and their social environment are offered to social workers.